Pengaruh Sustitusi Silase Rumput Kume dengan Fodder Jagung Hidroponik terhadap Konsumsi dan Kecernaan Protein, NH3, dan Urea Darah Kambing Kacang Jantan - Nomleni, Mahli; Jelantik, I Gusti Ngurah; Benu, Imanuel (Animal Agricultura, 2024)
The purpose of this study was to evaluate the effect of substitution of kume grass silage with hydroponic corn fodder on protein consumption and digestibility, NH3-N concentration, and blood urea concentration of male kacang goats. Three male kacang goats aged around 11-12 monts (initial body weigh = 13,5-17,1 kg) were used in this study following a 3 x 3 Latin Square Design (RBSL) with 3 treatments and 3 periods as replication. The treatments tested were: FCG0 = 70% kume grass silage + 30% concentrate; FCG1 = 35% kume grass silage + 35% hydroponic corn fodder + 30%  concentrate; FCG2 = 20% kume grass silage + 50% hydroponic corn fodder + 30% concentrate. Data obtained from this study were analyzed using ANOVA followed by Duncan’s multiple distance test using SPSS 22. The result of this study indicated that replacing kume grass silage with hydroponic corn fodder had no significant effect (P>0.05) on protein consumption, protein digestibility, NH3-N concentration, and blood urea concentration in male kacang goats. It can be concluded that hydroponic corn fodder can replace kume grass silage up to 50% in the diet without changing protein utilization in male kacang goats.